Arginine methylation and binding of Hrp1p to the efficiency element for mRNA 3'-end formation - Valentini, Sandro Roberto [UNESP]; Weiss, Valerie H.; Silver, Pamela A. (Cold Spring Harbor Laboratory, 1999)
Hrp1p is a heterogeneous ribonucleoprotein (hnRNP) from the yeast Saccharomyces cerevisiae that is involved in the cleavage and polyadenylation of the 3'-end of mRNAs and mRNA export. In addition, Hrp1p is one of several RNA-binding proteins that are posttranslationally modified by methylation at arginine residues. By using-functional recombinant Hrp1p, we have identified RNA sequences with specific high affinity binding sites. These sites correspond to the efficiency element for mRNA 3'-end formation, UAUAUA. To examine the effect of methylation on specific RNA binding, purified recombinant arginine methyltransferase (Hmt1p) was used to methylate Hrp1p. Methylated Hrp1p binds with the same affinity to UAUAUA-containing RNAs as unmethylated Hrp1p indicating that methylation does not affect specific RNA binding. However, RNA itself inhibits the methylation of Hrp1p and this inhibition is enhanced by RNAs that specifically bind Hrp1p. Taken together, these data support a model in which protein methylation occurs prior to protein-RNA binding in the nucleus.
Keywords: Cleavage; Hmt1p; hnRNPs; Polyadenylation; RNA binding; arginine; messenger RNA; methyltransferase; ribonucleoprotein; ribonucleoprotein hrp1p; RNA binding protein; unclassified drug; binding site; cell nucleus; controlled study; nonhuman; polyadenylation; priority journal; protein methylation; protein RNA binding; reverse transcription polymerase chain reaction; RNA cleavage; RNA processing; RNA sequence; saccharomyces cerevisiae; Adenosine Triphosphatases; Amino Acid Sequence; Arginine; Base Sequence; Binding Sites; Cross-Linking Reagents; DNA Helicases; Heterogeneous-Nuclear Ribonucleoproteins; Kinetics; Methylation; Methyltransferases; Molecular Sequence Data; Oligoribonucleotides; Protein Binding; Protein Processing, Post-Translational; Recombinant Proteins; Ribonucleoproteins; RNA, Messenger; RNA-Binding Proteins; Saccharomyces cerevisiae